H31 Dysphagia in huntington´s disease – an observational study. (September 2018) - Schradt, Falk; Geitner, Carolin; Lang, Christina; Weydt, Patrick; Süßmuth, Sigurd; Lindner-Pfleghar, Beate; Landwehrmeyer, G Bernhard
Abstract : Background: In Huntington´s Disease (HD) swallowing functions become progressively impaired, increasing the risk of aspiration and broncho-pulmonary infections. Currently the widely held belief that swallow training (SLT) is beneficial in HD is not supported by adequate evidence. As a first step towards establishing at what disease stage SLT interventions are most beneficial we describe onset and characteristics of the swallowing disorder in HD. Purpose and methods: We studied 73 consecutive HD patients attending the HD center of UUlm using the Clinical Swallowing Examination (CSE) & Fiberendoscopic Evaluation of Swallowing (FEES) in different stages of HD. Dysphagia was operationally defined as a score >2 on the Penetration-Aspiration-Scale (PAS). It was explored whether an increased risk of aspiration can be predicted by applying predictors established by Daniels for stroke patients and whether compensatory and adaptive methods are helpful interventions in HD. Results: As expected, patients in later stages of HD displayed a more severe dysphagia and precautions for oral intake were recommended; insertion of a Percutaneous Feeding Tube (PFT) was recommended more frequently in more advanced stages of HD (Chi-Quadrat Pearson p=0.001). In stages 3 & 4, 21 subjects exhibited dysarthria (>95%) and voice-change after swallow (>86%) as sensitive, but not very specific (<20%) clinical predictor. In addition, tongue movement disorder predicted a PAS>2 (sensitivity>86%). To prevent aspiration, chin tuck swallowing as well as individual diet adaptation were effective in all stages of HD. There is a tendency for lower BMI in later stages. However, there was no significant correlation between the extent of dysphagia and BMI. Conclusions: Most patients with dysphagia in FEES exhibited dysarthria and tongue movement disorder. However, to exclude dysphagia with confidence, FEES should be employed; so far no reliable clinical predictor for penetration and aspiration in HD has been established. Chin tuck in combination with an appropriate diet adjustment allow HD patients a safe oral feeding.